The Effect of Rehabilitation Exercises Using DRX9000 Spinal Decompression Device on the Rehabilitation of Lower Back Pain in Athletes Who Use Wheelchairs - Abdullah, Ali (Pubmedia Jurnal Pendidikan Olahraga, 2025)
Sports injuries are considered a significant issue for athletes in general and for individuals with disabilities in particular, as they represent a major factor affecting the physical performance of disabled individuals who engage in sports and physical activities. People with disabilities already experience limitations and reduced mobility due to their impairments, which increases their risk of injury during physical activity, whether from improper movements or actions that exceed their natural physical capacity. One common injury among wheelchair users in various sports is lower back pain, characterized by the onset of pain and limited mobility in the lumbar region. This condition can impede athletic performance, leading to temporary cessation of sports activities until the pain subsides. Recurrent episodes may result in complications or more severe injuries. Even minor lower back pain, if not addressed with appropriate medical and therapeutic measures, can develop into a serious condition. Through a review of existing literature, the researcher observed that current rehabilitation and treatment programs for lower back injuries may not adequately meet the specific needs of individuals with disabilities. Therefore, the researcher designed a set of exercises tailored to the physical capabilities of wheelchair users, incorporating the programmed spinal traction device (DRX9000) and additional assistive tools, under the supervision of a specialized orthopedic physician and physiotherapy experts.